Sistema de gestión del conocimiento para instituciones de educación superior. Caso Corporación Universidad de la Costa-CUC (2024)
In the current business environment, knowledge has become a fundamental strategic asset for the success and competitiveness of organizations. The ability to acquire, create, store, share, and apply knowledge effectively has become crucial for innovation, continuous learning, and informed decision-making. It is in this context that the need arises to develop and apply a knowledge management model that allows organizations to maximize the value of their collective intellect. This research proposes a knowledge management model with a comprehensive and systematic structure to address the challenges associated with managing intangible assets within an organization. This model is based on the premise that knowledge, when managed efficiently, becomes a driver of innovation and competitive advantage. By focusing on aspects such as acquisition, creation, storage, transfer, and application of knowledge, this model aims to provide a practical and effective guide for organizations seeking to optimize their knowledge management processes. To achieve this, a descriptive scope research was proposed, with the objective of identifying and describing the characteristics of knowledge management in the Higher Education Institution (HEI) under study and promoting mechanisms to appropriate the relevant knowledge that allows achieving greater competitiveness in the sector. Under a methodology consisting of identification, analysis, and design of a knowledge management model proposal. This research will be conducted through a descriptive scope, under a positivist paradigm, with a quantitative approach and a non-experimental, cross-sectional design. To obtain the results, a research tool such as a survey was used, where results were obtained that allowed highlighting the need for the model to implement a set of mechanisms to systematize the acquisition and transfer of knowledge within the university. Creating and fostering spaces for continuous feedback that allows the dissemination of ideas, innovative practices, and research findings, which will enrich not only the application of knowledge but also drive the professional growth of participants. Similarly, developing effective strategies to improve the dissemination of publications and other knowledge products generated by the University, among other results. Therefore, it is concluded that the Knowledge Management Model for the HEI should integrate continuous feedback as a key to identifying areas for improvement, fostering interdisciplinary collaboration, and strengthening the intellectual fabric. Likewise, developing effective strategies to improve the dissemination of publications and other knowledge products generated by the university. The goal is to create an environment conducive to innovation, skill development, and optimization of collective knowledge. This, in turn, will strengthen its position as a leading institution in higher education and in the generation of high quality knowledge, which is essential for academic and scientific progress